Pathological mechanisms of glial cell activation and neurodegenerative and neuropsychiatric disorders caused by Toxoplasma gondii infection - Yang, Zihan; Chen, Jiating; Zhang, Chi; Peng, Hongjuan (Frontiers in Microbiology, 2024)
Toxoplasma gondii is an intracellular opportunistic parasite that exists in a latent form within the human central nervous system (CNS), even in immune-competent hosts. During acute infection, T. gondii traverses the blood–brain barrier (BBB). In the subsequent chronic infection phase, the infiltration of immune cells into the brain, driven by T. gondii infection and the formation of parasitic cysts, leads to persistent activation and proliferation of astrocytes and microglia. This process results in neuronal damages that are fatal in some cases. Through inducing systemic immune responses, T. gondii infection can dramatically alter the behavior of rodents and increase the risk of various neuropsychiatric disorders in humans. In this review, we explore some recent research progress on the major events involved in BBB disruption, glial cell activation and neuronal damage following T. gondii infection in hosts. It further discusses potential pathological mechanisms and the feasible treatment approaches for the neurodegenerative and neuropsychiatric disorders caused by T. gondii infection to extend our understanding for pathogenesis and preventive control of toxoplasmosis in humans.